ANALISIS KARAKTERISTIK MUTU SABUN TRANSPARAN BEKATUL BERAS MERAH (Oryza nivara) BERBAHAN DASAR MINYAK GORENG BEKAS - Maria Mita Susanti; Syela Puspitaningtyas (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACT The free radicals exposure from daily activities can cause the damage the skin, therefore to avoid this damage effect can use antioxidants compounds . Brown rice bran is rice milling waste which has high antioxidant with IC50 is 43,2349 ppm. Efforts to increase the economic value of rice bran high in antioxidant compounds is by processing rice bran into transparent soap products. This research was conducted to analyze the quality characteristics of transparent red rice bran soap (Oryza nivara) based on used cooking oil. The quality characteristics of transparent rice soap which includes organoleptic soap, pH, foam power, free alkali, and water content. The data were analyzed descriptively by comparing the results of research with SNI 06-3532 -1994 Based on the results of the study obtained the results of the characteristics of soap that meets the quality characteristics of SNI 06-3532-1994 soap requirements with a pH of 10,2 , foam power of 2,54 cm, free alkali of 0,034%, and 3,85% moisture content. Keywords : transparent soap, brown rice bran, used cooking oil, solid soap quality characteristics